Formation and Application of Core–Shell of FePt-Au Magnetic–Plasmonic Nanoparticles - Wei, Da-Hua; Lin, Tei-Kai; Liang, Yuan-Chang; Chang, Huang-Wei (Frontiers in Chemistry, 2021)
Monodispersed FePt core and FePt–Au core–shell nanoparticles (NPs) have been chemically synthesized in liquid solution and with controllable surface-functional properties. The NP size was increased from 2.5 nm for FePt to 6.5 nm for FePt–Au, which could be tuned by the initial concentration of gold acetate coated onto FePt seeding NPs via a seed-mediated formation of self-assembled core–shell nanostructures. The analyses of the interplanar spacing obtained from the high-resolution transmission electron microscopy (HRTEM), selective electron diffraction pattern (SAED), and x-ray diffraction (XRD) confirmed that both FePt core and Au shell belong to the face-centered cubic (fcc) structure. FePt–Au NPs have a surface plasmon resonance (SPR) peak at 528 nm in the visible optical band region, indicating the red shift compared with the typical theoretical value of 520 nm of pure Au NPs. The surface modification and ligand exchange of FePt–Au was using mercaptoacetic acid (thiol) as a phase transfer reagent that turned the NPs hydrophilic due to the functional carboxyl group bond on the surface of presented multifunctional magnetic–plasmonic NPs. The water-dispersible FePt-based NPs conjugated with biomolecules could reach the different biocompatibility requirements and also provide enough heating response that acted as a potential agent for magnetic fluid hyperthermia in biomedical engineering research fields.